GERAK LAJU SEJARAH DALAM PANDANGAN FILSAFAT KARL MARX - Suparman Arif; Rinaldo Adi Pratama; Yusuf Perdana (Universitas Galuh, 2020)
In Karl Marx’s view, the economic activity of society is the basis as a driving factor for historical movement. Marx revealed that the historical movement occurred because of the conflict of social classes in society. The social class is a pattern of historical movement. The method used is a historical method that includes heuristics, critics, interpretation and historiography. This article addressed three main problems, the movement of human activity as a pattern of historical movement, the basic foundation of philosophy as a driving force, and the ultimate goal of historical movement.